Progressive skin necrosis of a huge occipital encephalocele - Andarabi Yasir; Nejat Farideh; El-Khashab Mostafa (Indian Journal of Plastic Surgery)
Objects: Progressive skin necrosis of giant occipital encephalocoele is an extremely rare complication found in neonates. Infection and ulceration of the necrosed skin may lead to meningitis or sepsis. We present here a neonate with giant occipital encephalocoele showing progressive necrosis during the first day of his life. Methods: A newborn baby was found to have a huge mass in the occipital region, which was covered by normal pink-purplish skin. During the last hours of the first day of his life, the sac started becoming ulcerated accompanied with a rapid color change in the skin, gradually turning darker and then black. The neonate was taken up for urgent excision and repair of the encephalocele. Two years after the operation, he appears to be well-developed without any neurological problems. Conclusion: Necrosis may have resulted from arterial or venous compromise caused by torsion of the pedicle during delivery or after birth. The high pressure inside the sac associated with the thin skin of the encephalocoele may be another predisposing factor. In view of the risk of ulceration and subsequent infection, urgent surgery of the necrotizing encephalocele is suggested.